A world in a grain of sand: human history from genetic data - Colonna, Vincenza (BioMed Central, 2011)
Genome-wide genotypes and sequences are enriching our understanding of the past 50,000 years of human history and providing insights into earlier periods largely inaccessible to mitochondrial DNA and Y-chromosomal studies. To see a world in a grain of sand ... William Blake, Auguries of Innocence